Perceptions of ethically ambiguous public relations practices on social media - Anna Klyueva; Prisca Ngondo (Communicare)
This research explored views on ethically acceptable public relations (PR) practices on social media held by Zimbabwean PR practitioners. There are several distinct findings that provide insight into PR practice and inform future studies on the role of social media in PR in the region. First, Zimbabwean practitioners were not unanimous in their assessment of whether examples of social media practices can be considered ethically acceptable, suggesting that many ethically ambiguous practices are perceived as a norm. Second, Zimbabwean PR practitioners overwhelmingly stressed the need for social media training and organisational policy to engage on social media ethically. Finally, practitioners believed that social media promoted the role and status of PR within organisations and afforded increased control over the reach and impact of organisational messages.